Simulation of the Logical Control System of Mobile Robots in a Fuzzy Environment - Mammadova, K.A.; Aliyeva, A.A. (Herald of Azerbaijan Engineering Academy, 2025)
In the realization of mobile robots, it is very important to apply a fuzzy logic control system for effective navigation and decision making in complex environments. The purpose of this paper is to investigate the steps of creating a fuzzy logic control system and different moments in time and select the optimal path. Fuzzy logic control systems are especially suitable for mobile robots due to the uncertainty and the possibility of approximate logical control. Unlike classical logical Boolean logic (true or false), fuzzy logic allows for varying degrees of accuracy, making it ideal for situations where binary true/false conditions are inadequate in real-world conditions. As a result of simulation studies conducted using MATLAB and Simulink programs, the capabilities of mobile robots to avoid obstacles and the degree of effectiveness of control systems based on fuzzy logic were determined.